Analisis Penerapan Biaya Volume Laba terhadap Perencanaan Laba Perusahaan (Studi Kasus pada Franchise C’bezt Fried Chicken Gedangan, Sidoarjo) - Dyah Oktaviani Sulistyaningrum Agustono; Muhamad Rizqi; Maria Y ovita R. Pandi; Slamet Riyadi (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze and calculate profit planning for the Cbezt Fried Chicken business in Gedangan, Sidoarjo. The research method used is descriptive qualitative. Primary data and secondary data were used in this research. Primary data was obtained through interviews and direct observation at Cbezt Fried Chicken. The research results show that to achieve the expected profit, the business unit needs to sell 14,557 pcs of fried chicken in 3 months or achieve revenue of Rp. 87,341,090. This means that daily sales must reach a minimum of 202 chickens or a daily sales target of Rp. 1,213,083 assuming selling days are 24 days a month. In conclusion, this research provides a clear view for business owners in planning sales strategies to achieve the expected profit targets. Keywords: CVP, Operating Leverage, Contribution Margin, Safety Margin